PERHITUNGAN BIAYA OVERHEAD PABRIK PADA CV.KRAMA AGUNG SAMARINDA - Sofiana, Sari Perdanawati widya (EKONOMIA, 2014)
In determaining the calculation of factory overhead costs and a description of the baground cv krama agung samarinda noble manners can be formulated problem is that the loading according to the company’s manufacturing overhead costs charged to factory overhead on the basis of 35% of the cost of raw materials,for each type of product while the amount of manufacturing overhead costs charged by the company in 2011 and 2012 amounted to Rp.67.200.000 and acceptance Rp.77.275.000 volumes 2011 and 2012 Rp.68.266.000 acceptance Rp.60.900.000 mold 2011 USD 6.300.000 and 2012 Rp.9.009.000. according to the result of the analysis of factory overhead costs factory overhead rates in 2011 and 2012 and Rp.77.275.000 Rp.67.200.000. this shows that the company is higher than the result of the analysis calculation. This suggests that the BOP charged in 2012 was higher than in 2011 with a growt rate of 14,99%